2008
DOI: 10.1002/pits.20300
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among stress, coping, and mental health in high‐achieving high school students

Abstract: This study investigates the relationships among stress, coping, and mental health in 139 students participating in an International Baccalaureate (IB) high school diploma program. Mental health was assessed using both positive indicators (life satisfaction, academic achievement, academic self-efficacy) and negative indicators (psychopathology) of adolescent social-emotional and school functioning. Findings include that students in an IB program perceive significantly more stress than a sample of 168 of their g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
161
2
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(182 citation statements)
references
References 42 publications
(48 reference statements)
9
161
2
10
Order By: Relevance
“…Our findings thus seems contradictory to US findings that individuals attending schools with higher academic demands experience more perceived stress (Kaplan et al, 2005;Suldo et al, 2008). However, there are important differences between the studies: there are cultural differences between the US and Swedish schools and the two Swedish schools are fully comparable in terms of curriculum, which is not the case in the study of American schools by Suldo et al…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Our findings thus seems contradictory to US findings that individuals attending schools with higher academic demands experience more perceived stress (Kaplan et al, 2005;Suldo et al, 2008). However, there are important differences between the studies: there are cultural differences between the US and Swedish schools and the two Swedish schools are fully comparable in terms of curriculum, which is not the case in the study of American schools by Suldo et al…”
Section: Discussioncontrasting
confidence: 56%
“…While there is no Swedish evidence covering this suggestion, in the USA, Suldo et al showed that students following the high achieving International Baccalaureate curriculum perceived more stress than students in the general education curriculum due to higher academic demands, but this higher perceived stress did not reduce academic performance. The absence of a reduction in performance was suggested to be due to adaptive coping strategies (Suldo, Shaunessy, & Hardesty, 2008). Kaplan et al, on the other hand, state that for students in high stress school environments in the USA an increase in academic expectations may serve to increase school-related stress and reduce academic performance (Kaplan, Liu, & Kaplan, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The difference in findings may be attributed to the different kinds of problems faced by adolescents from normal secondary schools in comparison to boarding school students, one of which includes the increased perceptions of stress in an academically demanding curriculum (Suldo et al, 2008). Other than that, the difference in sample selection, which involved different age groups, the factor of examination year and different questionnaires used, could have also contributed to the difference in findings.…”
Section: Discussionmentioning
confidence: 68%
“…Finally, when selecting the study population we opted for two schools that differed in terms of socioeconomic status, academic proficiency profile, urbanicity, and geographic location with the aim of getting a sample as representative as possible. This has been asked for in previous studies (Schraml, Perski, Grossi, & Makower, 2012;Suldo et al, 2008).…”
Section: Limitations and Strengthsmentioning
confidence: 98%
“…Measurements of perceived stress are reported to have higher ecological validity than physiological response parameters and self-report of psychiatric symptoms (Lavoie & Douglas, 2012). The PSS has been empirically validated in college students (Lee, 2012) and has been used in adolescents in clinical and normal populations to predict outcomes such as depression, anxiety and underachievement (Suldo, Shaunessy, & Hardesty, 2008). For comparison, we used the mean score for Swedish university students (mean age 25.4 years) from a 1996 validation study of the translation of the questionnaire into Swedish, where both males and females scored 24.4 on the PSS scale (Eskin & Parr, 1996).…”
Section: Questionnaires and Computer Programsmentioning
confidence: 99%